Mapping Determinant Factor and Minimizing the emergency Off a single candidate in Regional election: a case in buton - Junaid Gazalin; Nur Inzana; La Asiri La Asiiri; Sry Mayunita; Tawakkal Baharudin (Universitas Muhammadiyah Tangerang, 2025)
This study aims to analyze the factors that encourage the emergence of single candidates in regional head elections (Pilkada) in Buton and provide strategic steps to minimize the potential for a similar phenomenon to recur. This study uses a qualitative approach with a case study. A total of 20 informants were interviewed and selected purposively based on their direct involvement in the election process. Data analysis was carried out with the help of Nvivo 12 Plus software to optimize data management and interpretation. Data validity was maintained through source triangulation. The study results indicate that dominant factors such as high political costs, failure of the political party cadre system, pragmatism of political party coalitions, and the difficulty of individual candidates in meeting nomination requirements play a central role in the emergence of single candidates. The implications of this study emphasize the need to improve the mechanism for monitoring political costs, improve the quality of the political party cadre system, revise the nomination requirements for individual candidates, and increase awareness of the importance of forming a healthy and politically representative coalition. The significance of this study lies in its contribution to providing in-depth understanding and strategic recommendations to prevent the recurrence of the single candidate phenomenon in the Pilkada contest, especially in Buton Regency.Â Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mendorong kemunculan calon tunggal dalam pemilihan kepala daerah (Pilkada) di Buton serta memberikan langkah-langkah strategis untuk meminimalkan potensi terulangnya fenomena serupa. Penelitian ini menggunakan pendekatan kualitatif dengan strategi studi kasus. Sebanyak 20 informan diwawancarai, yang dipilih secara purposive berdasarkan keterlibatan langsung dalam proses pemilihan. Analisis data dilakukan dengan bantuan perangkat lunak Nvivo 12 Plus guna mengoptimalkan pengelolaan dan interpretasi data. Validitas data dijaga melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa faktor dominan seperti tingginya biaya politik, kegagalan sistem kaderisasi partai politik, pragmatisme koalisi partai politik, dan kesulitan calon perseorangan dalam memenuhi syarat pencalonan, memainkan peran sentral dalam kemunculan calon tunggal. Implikasi dari penelitian ini menekankan perlunya perbaikan mekanisme pengawasan biaya politik, peningkatan kualitas sistem kaderisasi partai politik, revisi terhadap persyaratan pencalonan bagi calon perseorangan, serta peningkatan kesadaran akan pentingnya pembentukan koalisi yang sehat dan representatif secara politik. Signifikansi penelitian ini terletak pada kontribusinya dalam memberikan pemahaman yang mendalam serta rekomendasi strategis guna mencegah terulangnya fenomena calon tunggal dalam kontestasi Pilkada, khususnya di Kabupaten Buton.